The Influence of Early Childhood Education Teachers' Academic Qualifications on the Quality of Learning at Insan Prima National Kindergarten, Cikarang, Bekasi - Venus Wanudyaningsih Kanugrahan; Daniel S. Tjandra (Manajia: Journal of Education and Management, 2025)
Early childhood education (PAUD) has a very important role or function in building the foundation of children's intelligence, social and emotional skills. Therefore, the quality of education provided at this stage requires special attention, especially in terms of the quality of PAUD teachers. PAUD teachers not only act as teachers, but also as facilitators who guide the cognitive, social and emotional development of their students. The main factor influencing the quality of the learning process in ECED is the teacher's educational background or teacher academic qualification. PAUD teacher education encompasses a range of knowledge and skills required to design, implement and evaluate learning in line with children's developmental needs. PAUD teachers who have a good educational background can create a fun, safe and stimulating learning environment for children, At last the teacher's educational background can affects to develop of the child. This research aims to determine and describe the influence of PAUD teachers' educational background on the quality of learning. By using qualitative methods in the form of interviews and direct observation to see the influence of PAUD teachers' educational background on the quality of learning. The conclusion of this research shows that teachers who have formal education in the field of PAUD, especially S1 PAUD, are more effective in managing the classroom, designing learning, and using media relevant to child development.